Length of transmission lag from monetary policy rate (MPR) and broad money supply (M2) to inflation in Nigeria - Yakubu Alfa; Suleiman Sa'ad; Zubair Abdulrasheed (West African Journal of Monetary and Economic Integration, 2021)
This study examines the length of transmission lag from monetary policy rate and money supply to inflation in Nigeria between the periods of January 2007 to March 2018. Using Autoregressive Distributed Lag (ARDL) model, the study reveals that changes in MPR does not transmit instantly to inflation but does so only after delaying for sometimes, changes in the operating targets only impact on the ultimate target (inflation) after long period. It takes changes in MPR about 20 months to impact significantly on inflation, similarly, changes in M2 takes about 25 months to influence inflation in Nigeria. This suggest that the new operating framework (MPR) introduced by the Central Bank of Nigeria (CBN) does not effectively impact on inflation within the desired period. Therefore, it is recommended that the operating framework be streamlined to ensure the reduction in the transmission lag of monetary policy to inflation in Nigeria.
Keywords: 330; Monetary policy lag; MPR. M2; ARDL